Analysis of the Integration and Innovation of Information Technology in Archive Management - Li, Hui (Journal of Theory and Practice of Management Science, 2024)
With the development and progress of society, modern science and technology has made a breakthrough, modern society has fully entered the information network era, the development and application of information technology in all fields of society has reconstructed the social industrial structure. Information technology has natural advantages in information transmission, sorting and analysis, and can quickly integrate a large amount of information together, which brings great convenience to archives management. In recent years, with the help of information technology and related resources, archives management has eliminated the disadvantages of traditional management mode and optimized the archives service. the “one belt, one road” initiative is the result of the profound transformation of economic development, the profound change of development pattern and the cultural exchange and interaction in different countries. From the perspective of “one belt, one road” to enhance the discourse dimension of cultural confidence, the historical context and the space‐time pattern are the dimensions of the cultural confidence. The historical materialism and materialist dialectics are the philosophic dimensions of enhancing the cultural confidence under the “one belt and one road” initiative. It provides important opportunity for the economic, political and cultural development of the countries along the line, which is the value dimension of the “one belt and one road”. At present, "one belt, one road" initiative to enhance cultural confidence is faced with a realistic challenge in the ideological field, such as complex situation, weak cultural and external communication power, and difficulties in guiding public opinion in cyberspace. To solve these difficulties, first, we should consolidate the mainstream ideology of Marxism; second, we should strengthen the construction of foreign discourse system; third, we should pay attention to the construction of ideological and cultural positions on the Internet.